Malaysian Investments in China: Transnationalism and the 'Chineseness' of Enterprise Developement - Edmund Terence Gomez (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
The concept of transnationalism is characterised by an important contradiction. While it makes an important contribution to the literature on identity by focussing on the themes of hybridity and pluralism, when it discusses the issue of transnational capital, it falls into the trap of essentialising ethnicity. Transnational theorist argue that there exists a pan-ethnic unity among the Chinese diaspora that would enable this community to emerge as a new economic force globally. The case studies in this essay reveal, however, that transnational networks do not influence the way ethnic groups do business with co-ethnics in other countries. This study argues that there is significant competition among Chinese-owned enterprises, which explains the dynamism of these firms. There is also much evidence of inter-ethnic corporate ties involving Chinese firms. These findings bring into question the importance of common ethnic identity in transnational business transactions undertaken by the Chinese companies. Keywords: Transnationalism, Chinese Identity, Networks, Enterprise Development.
hdl:10398/7404
Keywords: 330